Cimate Breakdown sebagai Mafsadah Kubra: Rekonstruksi Maqashid al-syari'ah al-Syatibi untuk Keadilan Ekologis Global - Filda Rossa; Dahyul Daipon; Fahmil Samiran; Putri Handayani; Muhammad Ridha (Universitas Islam Negeri Sumatera Utara, 2026)
Climate breakdown has evolved beyond an environmental concern into a systemic global crisis that threatens the sustainability of human civilization. Although a growing body of scholarship has examined the relationship between climate change and maqasid al-shariʿah, existing studies predominantly treat climate change as a threat to the five essential objectives (al-kulliyyat al-khams) without critically examining its normative status within the theory of mafsadah or its implications for the reconstruction of Islamic legal methodology. This study aims to reconstruct the normative position of climate breakdown within al-Syatibi’s maqasid al-shariʿah framework and to formulate a methodological paradigm capable of addressing contemporary ecological crises. Employing normative legal research through conceptual and philosophical approaches, the study analyzes al-Syatibi’s al-Muwafaqat in dialogue with contemporary maqasid scholarship, particularly the works of Ibn ʿAshur, Jasser Auda, Mohammad Hashim Kamali, Ibrahim Ozdemir, and Fazlun Khalid, while incorporating current scientific evidence on climate change drawn from authoritative environmental reports. The findings demonstrate that climate breakdown constitutes mafsadah kubra because its impacts are systemic, transboundary, intergenerational, cumulative, and simultaneously undermine the realization of all maqasid al-ḍaruriyyah. Furthermore, the study identifies ecological vulnerability as the missing conceptual link that explains how climate breakdown evolves into a comprehensive disruption of the objectives of Islamic law. Building upon these findings, the article proposes ecological ijtihad as a new methodological paradigm that integrates maqasid al-shariʿah,, scientific evidence, ecological vulnerability, and global ecological justice into Islamic legal reasoning. The originality of this research lies in reconstructing the concept of mafsadah within al-Syatibi’s framework and expanding the scope of maqasid al-shariʿah,from safeguarding individual interests to protecting the ecological life-support system as the normative foundation of sustainable justice.